UNVEILING THE DYNAMICS OF THE 2024 MAIDUGURI FLOOD DISASTER: CAUSES, IMPACTS, PERCEPTIONS AND COMMUNITY COPING STRATEGIES - Gloria Oduifa Otouaye (World Journal of Biology Pharmacy and Health Sciences, 2026)
This study unveils the dynamics of the 2024 Maiduguri flood disaster, assessing its root causes, extensive impacts, and the coping strategies adopted by affected communities. Fieldwork was conducted across heavily impacted areas, including Alau Dam, Galtimari, Fori Bridge, and Shetimari. The findings reveal that the disaster was primarily triggered by heavy rainfall and the subsequent collapse of the Alau Dam, exacerbated by poor urban planning, inadequate drainage systems, and climate change. The floods caused severe infrastructural damage, property loss, and public health risks, displacing over 400,000 individuals. Containment and relief efforts by government agencies and non-governmental organizations were evaluated, highlighting logistical shortcomings and inequitable resource distribution. The study recommends robust interventions, including the enforcement of strict urban development codes, regular maintenance of drainage and dam infrastructure, and the adoption of international best practices such as the 'Sponge City' concept and green infrastructure. These proactive measures are critical to enhancing community resilience and mitigating the impact of future flood occurrences.